Krisis Legitimasi Politik Donald Trump Sebagai Ancaman Supremasi Amerika Serikat Dalam Politik Global - Sahide, Ahmad (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
Donald Trump is the 45th President of the United States who was sworn in on January 20, 2017. Donald Trump's victory shook the global political order because a number of his statements and political policies were very controversial. A number of controversial Trump policies include the recognition of Jerusalem as the capital of Israel, the closeness of relations with Vladimir Putin, to protectionist policies that get resistance from within and outside the country. The author uses the legitimacy theory in this study to see the political impact of the policies taken by Trump. The results of this study see that Donald Trump's policy controversy has an impact on the crisis of political legitimacy which results in the threat of US political supremacy in the global political arena.